PENERAPAN MODEL EXAMPLE NON EXAMPLESEBAGAI UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPS DI SMP N 1 BATANG - Sudiami, Dinok (Harmony, 2018)
This research aims to improve the motivation and learning outcomes of human material and the environment by applying the example non example learning model. The data analysis method that be used is descriptive method by comparing the learning outcomes of students before the action with the learning outcomes of students after the action, and also comparing the motivation and learning outcomes of students in the first cycle and second cycle. The results showed that there is an increase in motivation and learning outcomes of students through the application of example non example models. The learning motivation of students has been increased as originally in the first cycle by 83.20% to 92.41% in second cycle. While, the learning outcomes of students from the research data also showed that there is also an increase with the level of classical completeness in the first cycle of 74.19% with an average value of 78.8 in the second cycle of classical completeness to the level of 83.87% with an average value of 82.   Penelitian ini bertujuan meningkatkan motivasi dan hasil belajar materi manusia dan lingkungan dengan penerapan model pembelajaran example non example. Metodeanalisis data yang digunakan yaitu metode deskriptif dengan membandingkan hasil belajar peserta didik sebelum tindakan dengan hasil belajar peserta didik setelah tindakan, serta membandingkan motivasi dan hasil belajar peserta didik pada siklus I dan siklus II. Hasil penelitian menunjukkan adanya  peningkatan motivasi dan hasil belajar peserta didik melalui penerapan model example non example. Motivasi belajar peserta didik mengalami peningkatan yang semula siklus 1 sebesar 83,20% menjadi 92,41% pada siklus II. Sedangkan untuk hasil belajar peserta didik dari data penelitian juga menunjukkan peningkatan dengan tingkat ketuntasan klasikal pada siklus I sebesar 74,19% dengan rata-rata nilai 78,8 pada siklus II tingkat ketuntasan klasikal sebesar 83,87% dengan rata-rata nilai 82.